2013
DOI: 10.1002/jgrd.50154
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring scan asymmetry of microwave humidity sounding channels using simultaneous all angle collocations (SAACs)

Abstract: [1] Simultaneous all angle collocations (SAACs) of microwave humidity sounders (AMSU-B and MHS) on-board polar orbiting satellites are used to estimate scan-dependent biases. This method has distinct advantages over previous methods, such as that the estimated scan-dependent biases are not influenced by diurnal differences between the edges of the scan and the biases can be estimated for both sides of the scan. We find the results are robust in the sense that biases estimated for one satellite pair can be repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
(37 reference statements)
3
31
0
Order By: Relevance
“…Far from nadir, channels sounding deep into the troposphere, located on the wings of the 183.31 GHz line, might be more affected by antenna issues than higher peaking channels, located in the center of the line, due to radiation measured by the side lobes. Such asymmetries were found for AMSU-B and MHS (Buehler et al, 2005b;John et al, 2013b), but so far the monitoring of SAPHIR has not shown any scan asymmetry. For ATMS, comparisons of temperature data records (TDRs, calibrated antenna temperatures) and sensor data records (SDRs, BT after further applying beam efficiency and scan-position-dependent bias corrections) for the 183 GHz channels show the same behavior meaning that the TDR to SRD conversion is not responsible for the bias, although it seems to introduce some dependence on the viewing angle that warrants further investigation.…”
Section: Scan Asymmetrymentioning
confidence: 85%
“…Far from nadir, channels sounding deep into the troposphere, located on the wings of the 183.31 GHz line, might be more affected by antenna issues than higher peaking channels, located in the center of the line, due to radiation measured by the side lobes. Such asymmetries were found for AMSU-B and MHS (Buehler et al, 2005b;John et al, 2013b), but so far the monitoring of SAPHIR has not shown any scan asymmetry. For ATMS, comparisons of temperature data records (TDRs, calibrated antenna temperatures) and sensor data records (SDRs, BT after further applying beam efficiency and scan-position-dependent bias corrections) for the 183 GHz channels show the same behavior meaning that the TDR to SRD conversion is not responsible for the bias, although it seems to introduce some dependence on the viewing angle that warrants further investigation.…”
Section: Scan Asymmetrymentioning
confidence: 85%
“…Consequently, potential non-linear effects as a function of scene brightness temperature are not considered. It has also been shown that there might be scan asymmetry in the AMSU-B brightness temperatures (Buehler et al, 2005;John et al, 2013), which has not been accounted for here.…”
Section: Assumptions and Known Limitationsmentioning
confidence: 91%
“…For example, there was a radio-frequency interference (RFI) problem in CH#3 and CH#4 of AMSU-B (Atkinson, 2001;Buehler et al, 2005), and gain variations/degredations are found in CH#3-CH#5 of AMSU-B on NOAA-16 and NOAA-17 (John et al, 2013). MHS exhibits smaller scandependent biases than AMSU-B, but suspicious behaviors have been reported for CH#3 on NOAA-18 and NOAA-19 and Metop-A (John et al, 2013). The MHS instruments on NOAA-18 and Metop-A have so far shown the best overall radiometric calibration for all five channels.…”
Section: Description Of Data Sets and Modelsmentioning
confidence: 99%